Pengembangan Kompetensi Membaca Al- Qur’an Pengajar Madin Melalui Metode An-Nahdliyah TPQ Sabilul’ilmi Pomahan Pulung - Wafik Nurul Khoiriyah; Nanik Setyowati; Samsudin Samsudin (Social Science Academic, 2025)
This article aims to find out how effective teachers in teaching the AL- Qur’an by using the An Nahdliyah method to increase the motivation to learn the Koran of children at TPQ Sabilul Huda village pomahan sub-district pulung ponorogo district. This article is motivated by the phenomenon that often occurs in the present time is the decline or low motivation of children in learning the Qu’ran. The research method used is a qualitative approach to the type of field research (field research). Data collection techniques using observation techniques, interviews and documentation. For data analysis using the theory of Miles Huberman and Saldana, namely: condensation data, data presentation and drawing conclusions. While the validity of the data using Triangulation sources and triangulation techniques.This research concludes Application of the An-Nahdliyah Method Improving Al-Qur'an Learning Ability in the Sabilul 'Ilmi is carried out according to the teachings of the an-nahdliyah method and innovation from ustadz ustadzah who teaches there. Where, in improving the quality of reading Al-Qur'an students through an-nahdliyah method, ustadz and ustadzah use the makhorijul letter demonstration method,Repeat reading of students who are not fluent. While in improving quality writing Al-Qur'an students, ustad and ustadzah create new innovations with the An-Nahdliyah method through the stages of spelling and connecting makhorijul letters. whereas learning or studying is an obligation for every Muslim from birth to close age. Most people do not care about religious education, especially in the scope of reading the Koran. seeing from this problem, of course, we need to find out how to make children not bored and enthusiastic in learning the Koran, this research is a type of descriptive qualitative research with interview and documentation methods. The results showed that the An Nahdliyah method was effectively applied at TPQ Sabilul 'ilmi Pomahan Village, this can be seen from the results of the study, increasing the ability to read the Koran and the enthusiasm of the students at TPQ Sabilul 'ilmi.